(untitled) (World Economics and Finance Bulletin, 2022)
Planning budgets are one of the methods used by the administration in controlling the elements of costs represented by (direct material costs, direct wage costs, and indirect manufacturing costs), and their importance lies in that they reflect what the activity of the economic unit should be in the future. In order to achieve the objectives of the economic unit and to solve this problem, the research was based on the following hypothesis (the role of planning budgets in controlling the elements of costs). , and thus the ability to reduce these costs and thus achieve profits by increasing sales and increasing market share, and the need to urge the state to support the company and the manufacturing sector, which helps and contributes to creating new marketing and sales outlets, and to focus on conducting courses, workshops and scientific seminars for employees in developing the professional and applied aspect for cost accounting .